Image of nursing held by nursing students according to gender: A qualitative study - ALPAR, ŞULE (WILEY, 2012)
This paper is a report of a study to determine the nursing images of female and male nursing students. The study used a qualitative research design to determine nursing images of male (n?=?20) and female (n?=?20) nursing students. To analyse the data, the method used content analysis. Statements were organized under three categories and seven themes after content analysis. The first category, nursing concept, incorporates the two themes of: (i) female or sister; (ii) job definition. The second category, choosing, incorporates the four themes of: (i) Desire of Others; (ii) Guarantee of Work; (iii) Being Helpful to Others; and (iv) Limited to Academic Achievement. The third category, Gender, incorporates the one theme of: (i) Gendered Approach. Male students have started to take part in nursing programs relatively recently; therefore, more research is needed in the fields of academic accomplishments of male students.
Keywords: focus group; gender; image; nursing; student nurse; MALE NURSES; UNDERGRADUATE; EXPERIENCES